Candidate circulating microRNAs as potential diagnostic and predictive biomarkers for the monitoring of locally advanced breast cancer patients - Alaa M Ibrahim; Mahmoud M Said; Amany M Hilal; Amina M Medhat; Ibrahim M Abd Elsalam (Tumor Biology)
This study aimed at investigating the expression of candidate microRNAs (miRs), at initial diagnosis, during neoadjuvant chemotherapy, and after the tumor resection in locally advanced breast cancer patients. Plasma samples were collected from locally advanced breast cancer patients (n = 30) and healthy subjects (n = 20) for the detection of candidate miRs’ expression using the real-time quantitative polymerase chain reaction. At initial locally advanced breast cancer diagnosis, the expression of miR-21, miR-181a, and miR-10b was significantly increased, whereas that of miR-145 and let-7a was significantly decreased, compared to the healthy individuals. The diagnostic accuracy of miR-21 was superior to both carcinoembryonic antigen and carcinoma antigen 15-3 as diagnostic biomarkers for locally advanced breast cancer. By the end of the treatment, the expression of altered miRs rebound to control values. The expression levels of candidate plasma miRs are useful diagnostic biomarkers, as well as monitoring a proper response for locally advanced breast cancer patients to the treatment. Furthermore, miR-10b and miR-21 can be considered as predictive biomarkers for progression-free survival.